SOME ASPECTS OF EVALUATING THE IMPACT OF ECOLOGICAL FACTORS ON THE ILLNESS OF THE POPULATION OF KARAKALPAKSTAN - Zhumamuratov, M.A.; Kudiyarova, G.Zh. (SCIENCE and SOCIETY, 2026)
The article examines the results of the analysis of the relationship between the health indicators of the population of Karakalpakstan and the environment. Comparative analysis of respiratory morbidity dynamics among the population showed that there is a marked increase in respiratory morbidity. It has been established that disruptions in the ecological balance of the natural environment in the South Aral Sea region largely determine the state of the population's morbidity.
Keywords: public health; environment; anthropogenic impact; pollution; morbidity